Correction to: Certolizumab Pegol in the Treatment of Psoriasis and Psoriatic Arthritis: Preliminary Real-Life Data. Issue 1 (March 2018) - Dattola, Annunziata; Cannizzaro, Maria; Mazzeo, Mauro; Bianchi, Luca
Abstract In the original publication, part Fig. 3b and c were interchanged. The correct versions are given below.